2006
DOI: 10.1093/jpepsy/jsj114
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Effect of Intravenous Methotrexate Dose and Infusion Rate on Neuropsychological Function One Year after Diagnosis of Acute Lymphoblastic Leukemia

Abstract: Findings suggest that difficulties in working memory and nonverbal skills may be evident during the first year of treatment for ALL and that severity may be dependent on IV MTX dose and/or infusion rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 8 publications
0
37
1
Order By: Relevance
“…7,44 In the current study, verbal (Digit Span) and visual (Trail Making 4) attention measures were significantly weaker for survivors of ALL compared with the healthy controls, and these measures correlated (r Ͼ 0.420) with regional frontal white matter volumes, though the correlations did not reach statistical significance by using a P value of Ͻ. 01 in this small sample.…”
Section: Discussioncontrasting
confidence: 65%
“…7,44 In the current study, verbal (Digit Span) and visual (Trail Making 4) attention measures were significantly weaker for survivors of ALL compared with the healthy controls, and these measures correlated (r Ͼ 0.420) with regional frontal white matter volumes, though the correlations did not reach statistical significance by using a P value of Ͻ. 01 in this small sample.…”
Section: Discussioncontrasting
confidence: 65%
“…In contrast, other studies show cognitive difficulties in children treated with chemotherapy and also demonstrate worse performance in children treated with higher doses [Carey et al, 2007]. Although rehabilitation interventions have not been well studied in this population, some research suggests the potential to improve cognitive difficulties with intervention .…”
Section: Brain Tumors and Acute Lymphoblastic Leukemiamentioning
confidence: 87%
“…Although one expects large groups of children to have mean IQ scores that approximate the population mean of 100, ALL patients tend to obtain IQ scores above 100 when assessed within weeks of diagnosis. Baseline IQs range from 99 to 115 with Performance IQ slightly higher than verbal IQ in most cases [Soni et al, 1975;Stehbens and Kisker, 1984;Copeland et al, 1988;Brown et al, 1996;Jansen et al, 2005Jansen et al, , 2006Nathan et al, 2006;Carey et al, 2007]. Furthermore, siblings of ALL patients exhibit mean full scale IQs near 110 [Moss et al, 1981;Jannoun, 1983;Twaddle et al, 1983;Taylor et al, 1987;Giralt et al, 1992;Jansen et al, 2005].…”
Section: Methodological Issuesmentioning
confidence: 99%
“…On-treatment studies IQ scores of children on active CO treatment are at least average [Williams et al, 1986;MacLean et al, 1995;Krappman et al, 2007;Moore et al, 2008], with no evidence of decline over the course of treatment [Copeland et al, 1988;Dowell et al, 1989;Brown et al, 1996;Copeland et al, 1996;Carey et al, 2007]. However, difficulties with perceptual motor speed [Copeland et al, 1988[Copeland et al, , 1996, working memory [Carey et al, 2007], academic achievement [Brown et al, 1996], and fine motor skills [Dowell et al, 1989;Hockenberry et al, 2007] have been reported.…”
Section: Chemotherapy-onlymentioning
confidence: 99%